Exploring the anteceding impact of personalised social media advertising on online impulse buying tendency. (2019) - Dodoo, Naa Amponsah; Wu, Linwan
Online impulse buying is a critical factor that can result in desired outcomes for online retailers and advertisers. Personalisation is progressively being used in marketing practices on social media. However, largely unexplored is the potential relationship between personalisation and online impulse buying tendency on social media. This study provides insights about the significance of personalisation on social media as an antecedent of customer's online impulse tendency, an especially important topic for online retailers. Specifically, this study develops and tests a conceptual model using different factors to determine the predictive power of perceived personalisation of social media ads on online impulse buying tendency. A noteworthy finding from the survey was the positive influence of perceived personalisation of social media ads on perceived relevance, which subsequently predicted customer's online impulse buying tendency. Results also indicate the impact of perceived personalisation on perceptions of value, relevance and novelty of social media ads. Theoretical and practical implications are discussed.